Patterns of Myopia Progression in European Adults - Michael Moore, PhD, MSc; Gareth Lingham, PhD; Daniel I. Flitcroft, DPhil, MBBS; James Loughman, PhD (Ophthalmology Science)
Objective: Data regarding the progression of myopia and new-onset myopia in young adults are lacking. This study aims to describe the natural history of myopia development and progression in adults using anonymized electronic medical records from Irish optometric practices. Design: Longitudinal study. Subjects: Electronic medical record data were extracted from 40 Irish optometry practices with 18 620 (59.5% female) patients meeting the inclusion criteria. Methods: Refractive error change was determined among patients with multiple eye examination visits during the period January 1, 2003 to December 31, 2022. Patients aged 18 to 39 years, inclusive, at baseline and attending >1 eye examination with an interval of ≥11 months between visits and that were myopic at the final visit were included in the analysis. Annualized myopia progression in diopter (D)/year was assessed using linear mixed models with age, sex, baseline spherical equivalent refraction, and previous myopic progression as fixed effect covariates. The proportion of patients with unstable myopia (progression worse than −0.25 D/year) was determined. Main Outcome Measures: Proportion of adults across the age range 18 to 39 years with significant myopic progression. Results: Significant myopia progression (progression <−0.25 D/year) was noted in 10.7% of all myopes. The proportion of myopes with significant progression was clearly related to age with 19.9% of myopes in the youngest age group experiencing progression compared with 6.8% in the oldest age group. Higher proportions of myopic progression were also observed in high myopes with 1 in 12 high myopes (8.0%) exhibiting persistent fast myopic progression as adults (worse than −0.50 D/year). Of patients with emmetropia or hyperopia at baseline in this clinic-based population, 28.5% and 0.8% became myopic during the follow-up period. Conclusions: Although myopia has stabilized in most adults (>18 years of age), a sizeable proportion of younger adults and high myopes (of all ages) do progress at a clinically significant rate. Almost 3 times as many adults in youngest age group (18–24 years) experienced myopic progression when compared with the oldest age group (40–44 years). Consideration should therefore be given to exploring the efficacy and benefit of myopia management in this cohort of patients. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.